2017
DOI: 10.15210/sah.v5i2.10726
|View full text |Cite
|
Sign up to set email alerts
|

ATIVIDADE OVICIDA DO ÓLEO ESSENCIAL E DO EXTRATO HIDROALCOÓLICO DE Ocimum basilicum SOBRE NEMATÓDEOS GASTRINTESTINAIS DE OVINOS

Abstract: RESUMOcontrole dos helmintos gastrintestinais em ovinos, realizado exclusivamente através de anti-helmínticos, tem como consequência a seleção de populações de helmintos resistentes a praticamente todos os fármacos disponíveis. Isso tem motivado à busca de alternativas para controle, entre as quais destacamos a utilização de fitoterápicos. Neste contexto, o objetivo deste estudo foi avaliar a atividade ovicida in vitro do óleo essencial e do extrato hidroalcoólico de Ocimum basilicum em nematódeos de ovinos e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Inhibition of H. contortus egg hatch was previously demonstrated by the EO of one O. basilicum cultivar and associated with methyl chavicol and linalool as major compounds of the EO tested (Castro et al, 2017). In the present study, the EOs from Napoletano, Genovese and Ararat cultivars showed the highest anthelmintic activity, and they also contain methyl chavicol and linalool, as major compounds (table 1) Citral, a natural combination of the isomers neral and geranial, has been shown to be effective against several nematodes, including H. contortus, both isolated and as the major compound of EO (Hierro et al, 2006;Macedo et al, 2019).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Inhibition of H. contortus egg hatch was previously demonstrated by the EO of one O. basilicum cultivar and associated with methyl chavicol and linalool as major compounds of the EO tested (Castro et al, 2017). In the present study, the EOs from Napoletano, Genovese and Ararat cultivars showed the highest anthelmintic activity, and they also contain methyl chavicol and linalool, as major compounds (table 1) Citral, a natural combination of the isomers neral and geranial, has been shown to be effective against several nematodes, including H. contortus, both isolated and as the major compound of EO (Hierro et al, 2006;Macedo et al, 2019).…”
Section: Discussionmentioning
confidence: 82%
“…The EO of O. basilicum has several biological activities, such as antifungal (El-Soud et al ., 2015), antimicrobial (Lang & Buchbauer, 2012), antiprotozoal (Almeida et al ., 2007; Santoro et al ., 2007), insecticidal (Rodríguez-González et al ., 2019), acaricidal (Martinez-Velazquez et al ., 2011) and anthelmintic (Castro et al ., 2017). However, there are several basil cultivars with considerably different EO composition (Sharopov et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations